Reckoning - Kamaruddin, Siti Faridah; Abang Abdul Rahman, Dayang Hummida (Corporate Communication Unit, UiTM Mukah Campus, 2025)
'Reckoning' is a creative writing piece that explores the author's thoughts and feelings about writing. The poem delves into the author's internal struggle and contemplation, questioning the purpose and nature of their writing. It touches upon themes of doubt, fear, and the desire to understand oneself and one's creative output. The author grapples with the idea of producing something meaningful and productive, while also acknowledge the potential for negative outcomes. Ultimately, the poem reflects a journey of self-discovery and the challenging process of confronting one's own thoughts and the world around them.